Antibiotics for acute otitis media in children. - Glasziou, P; Mar, D; Sanders, S; Hayem, M (2004)
BACKGROUND: Acute otitis media is one of the most common diseases in early infancy and childhood. Antibiotic use for acute otitis media varies from 31% in the Netherlands to 98% in the USA and Australia. OBJECTIVES: The objective of this review was to assess the effects of antibiotics for children with acute otitis media. SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (CENTRAL); MEDLINE, Index Medicus (pre 1965), Current Contents and reference lists of articles from 1958 to January 2000. The search was updated in 2003. SELECTION CRITERIA: Randomised trials comparing antimicrobial drugs with placebo in children with acute otitis media. DATA COLLECTION AND ANALYSIS: Three reviewers independently assessed trial quality and extracted data. MAIN RESULTS: Ten trials were eligible based on design, only eight of the trials, with a total of 2,287 children, included patient-relevant outcomes. The methodological quality of the included trials was generally high. All trials were from developed countries. The trials showed no reduction in pain at 24 hours, but a 30% relative reduction (95% confidence interval 19% to 40%) in pain at two to seven days. Since approximately 80% of patients will have settled spontaneously in this time, this means an absolute reduction of 7% or that about 15 children must be treated with antibiotics to prevent one child having some pain after two days. There was no effect of antibiotics on hearing problems of acute otitis media, as measured by subsequent tympanometry. However, audiometry was done in only two studies and incompletely reported. Nor did antibiotics influence other complications or recurrence. There were few serious complications seen in these trials: only one case of mastoiditis occurred in a penicillin treated group. REVIEWER'S CONCLUSIONS: Antibiotics provide a small benefit for acute otitis media in children. As most cases will resolve spontaneously, this benefit must be weighed against the possible adverse reactions. Antibiotic treatment may play an important role in reducing the risk of mastoiditis in populations where it is more common.